Fired for Facebook…terminated for Tinder: dismissal for social media misconduct in New Zealand. (11th October 2021) - Sia, Sophie; Cornish, René; Tranter, Kieran
Abstract: This article reports the findings of a qualitative study of first instance New Zealand employment tribunal decisions concerned with employee dismissal for social media misconduct. There are two main findings. The first relates to the legal approach to employee dismissal for social media misconduct developing in New Zealand. The decisions show New Zealand decision-makers are following the approach in other jurisdictions of treating social media misconduct dismissals as involving a balance between public and private considerations of employment conduct and calculating harm in the employment relationship. However, the decisions do not only track the emerging legal approach to social media misconduct in employment. The decisions are also a record of how social media is affecting employment relations within New Zealand. They are not only legal but also social records. The second finding relates to what the decisions reveal about employment and social media in New Zealand. The sample showed something different from other similar studies. In New Zealand, there was a large cluster of decisions where social media facilitated gender-based harassment. This finding resonates with wider research into New Zealand workplaces that suggests an enduring toxic culture where gender-based harassment is normalized.